ART IN THE SERVICE OF THE CHURCH IN YORUBALAND OF SOUTH-WESTERN NIGERIA: AN APPRAISAL - Emi Rod Adoh; Babatunde Samuel Olufemi (European Scientific Journal, ESJ, 2014)
The association of artworks with religion is dated back to the pre-historic times. The Yoruba who live in south-western Nigeria have traditional religions which were serviced by local artists before the advent of Christianity in the area. Utilizing some Western artworks as well as traditional ones, which were produced by local artists/artisans with materials and tools derived from the immediate physical environment, the Christian missionaries built and decorated the early churches they constructed in Yorubaland during the nineteenth century A.D. Christian patronage increased from the 1980s in south-western Yorubaland with the founding and proliferation of Pentecostal Christian Ministries. The aim of this paper is to conduct a concise historical survey of Christian‘s patronage of art in the area. This is done with a view to revealing the extent to which art contributed to the success of Christian church liturgies and evangelism there. In the end it was observed that art has contributed immensely to the planting, growth and sustenance of Christianity in the end it was observed that art has contributed immensely to the planting, growth and sustenance of Christianity in Yorubaland of southwestern Nigeria.